Enhancing the band gap of an active metamaterial. (June 2017) - Reynolds, Matthew; Daley, Steve
Metamaterials have been the subject of significant interest over the past decade due to their ability to produce novel acoustic behaviour beyond that seen in naturally occurring media. As well as their potential in acoustic cloaks and lenses, of particular interest is the appearance of band gaps which lead to very high levels of attenuation across the material within narrow frequency ranges. Unlike traditional periodic materials which have been employed at high frequencies, the resonant elements within metamaterials allow band gaps to form within the long wavelength limit; at low frequencies where it is most difficult to design satisfactory passive isolation solutions. Hence, metamaterials may provide a path to high-performance isolation at low frequencies. Passively these band gaps occur over a narrow bandwidth, however the inclusion of active elements provide a method for enhancing this behaviour and producing attenuation over a broad band. A new type of active viscoelastic metamaterial is presented that achieves double negativity and could be employed as a high-performance vibration isolator at low frequencies. A mathematical method for manipulating the band gap profile is developed and a prototype is produced. The passive band gap is confirmed in the laboratory, and then by applying active control using optimised feedback filters it is shown that the region at which attenuation occurs around the band gap could be greatly enhanced whilst retaining the peak passive band gap performance. The active metamaterial demonstrates that a unified design philosophy matching the best features of active and passive functionality can achieve high levels of attenuation over wide frequency bands.